Endometriosis and an increased risk of malignancies - Aleksandra Maria Krasa; Magdalena Kozioł; Halina Piecewicz-Szczęsna; Mateusz Pawlicki; Anna Łopuszyńska; Paulina Krawiec; Ewa Piekarska (Kazimierz Wielki University, 2020)
Introduction: Endometriosis is a common gynaecological disorder associated with pelvic pain and sub-fertility, affecting 7-15% of women of reproductive age. The disease is defined as the presence of endometrial-like tissue outside the uterine cavity, primarily on pelvic organs. The aetiology of endometriosis is still uncertain. The disease rarely causes mortality, however, it may have a significant impact on a patient's quality of life. Moreover, several studies have consistently shown that endometriosis is associated with a higher risk of some types of malignancies. Results: Endometriosis shares several molecular characteristics with invasive cancer, such as inflammation, tissue invasion, angiogenesis, dysfunction of immune cells and pro-survival features. Studies have shown that ovarian cancer, especially clear cell, endometrioid and serous, has been associated with endometriosis. Furthermore, the risk of cancer of the uterine cervix has shown to be decreased and the results on the risk of the cancers of uterine corpus or breast are inconsistent. Among non‐gynecological cancers, melanoma of the skin, non‐Hodgkin‐lymphoma, brain and thyroid cancers have also been associated with endometriosis. Conclusions: Research results indicate that women with endometriosis have an increased risk for some types of malignancies, therefore, they should be under strict gynecological control, even many years after menopause. Further research is needed to prove the real risk of different types of malignant tumors among women with endometriosis. In addition, it is necessary to establish periodic examination schedules among these patients in order to prevent certain types of malignancies.